Reverse of Acute and Chronic Morphine Tolerance by Lithocholic Acid via Down-regulating UGT2B7 - Zizhao Yang; Li Li; Haihong Hu; Mingcheng Xu; Jingkai Gu; Zaijie Jim Wang; Lushan Yu; Su Zeng (Frontiers Media S.A., 2016)
Lithocholic acid (LCA) deposited in human livers always induces drastic pains which need analgesic drug, like morphine to release. Our research showed that LCA can effectively inhibit uridine 5'-diphospho-glucuronosyltransferase 2B7 (UGT2B7) in morphine tolerance-like human normal liver cells, HL-7702, then increase μ-opioid receptor (MOR) and calcium-calmodulin dependent protein kinase IIα (CaMKIIα) expression. In vivo assay, UGT2B7 was significantly repressed in the livers of acute or chronic morphine tolerance mice pretreated with LCA (10, 50 and 100 mg/kg, p.o.). To investigate the connections between LCA function performance and changes of UGT2B7 enzymatic activity in mice livers, two morphine metabolites, morphine-3-glucuronide (M3G) and morphine-6-glucuronide (M6G) were quantified by solid phase extraction (SPE)-HPLC-MS/MS. The result indicated no matter in acute or chronic morphine tolerance, the concentrations of M3G and M6G were all decreased, the later one fell even more. Besides that, 50mg/kg of LCA administration can prevent auto-phosphorylation of CaMKIIα at Thr286 in acute or chronic morphine tolerance mice prefrontal cortexes (mPFCs) due to synthesis increase of cyclic adenosine monophosphate (cAMP). As a consequence, UGT2B7 depression mediated by LCA can affect its selective catalysis ability to morphine, that may be responsible to acute or chronic morphine tolerance alleviation. These findings might assist to modify antinociception of morphine in clinic.